Enemy love and the reinvention of identity - Ekman, Katja (HTS teologiese studies, 2021)
This article investigates the reception of Jesus’ command to ‘turn the other cheek’ and ‘love your enemies’, as found in the Sermon on the Mount in Matthew 5:38–48, among Christian Palestinians. With the help of basic tools from the postcolonial discourse, structures of power, identity and subjectivity of these commands are examined. Although seeming to advocate a quiet acceptance of violence, the commands are interpreted as empowering calls to contribute to the transformation of the self, the other and the society. A person’s dignity is seen to be restored and the transition from reactivity to agency is made possible. At the same time as the commandment of love ensures the uncompromising work for mutual respect and affirmation of both parties’ humanness and creation in the image of God. Walter Wink helps to understand the logic of nonviolent resistance that the pericope is leading to in the eyes of the interviewees. In the last section, both the Bible text and the insights gained by the examination of its reception are condensed and further expanded by a theory of love inspired by Dorothee Sölle. This theory of love argues that love is not only a general approach to life, rather than a sentimental feeling, but the basic principle of life, the courage to continue to love where no reason or hope is left, just the will to remain and love into the void. This is interpreted to be the strongest kind of love and a tremendous empowerment in the reinvention of identity.Contribution: This article contributes to the examination of identity processes within the field of theology and Bible interpretation as liberation and empowerment. The ethical and political relevancy of Scripture is here actualised in the example of the Palestinian context where questions of identity, justice and agency are more important than ever.